Arthropod management tests
Publishes short reports on preliminary and routine screening tests for management of arthropods which may be harmful (e.g., pests and disease vectors of plants, animals and humans) or beneficial (e.g., parasitoids, predators and diseases of pests, honey bees, silkworm, etc.). Pest management methods reported in this publication may be those using chemical pesticides as well as other materials such as insect growth regulators, semiochemicals (pheromones, kairomones, etc.), traps, bio-control agents, pest-resistant plants and animals.